Pengembangan dan Implementasi Sistem Layanan Katering “Fitmeal” yang Terintegrasi dengan Platform Web untuk Mempermudah Akses dan Pemesanan Makanan Sehat - Andreas Obrien Saragih; Caesar Yoga Pratama; Zakhi Febriyan; Shinta Intan Diva Kharisma (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
The development of information technology has driven digital transformation in various sectors, including the catering industry. As public awareness of the importance of a healthy lifestyle increases, the need for practical, fast, and reliable healthy catering services is growing. Healthier consumption patterns have become a priority for many individuals, however, many catering service providers still rely on traditional ordering systems, such as by telephone or manual recording. This results in various problems such as delayed responses, recording errors, difficulties in order management, and inaccuracies in menu and nutritional information. This study aims to develop an integrated web-based healthy catering service system, named FitMeal, designed to address these issues. This system was developed using the Waterfall model method, which includes key stages such as needs analysis, system design, implementation, testing, and maintenance. By using this approach, the developed system is expected to run effectively and efficiently. The results show that the developed system can improve efficiency in the ordering process, reduce recording errors, and simplify order management by catering providers. One of the key features of the FitMeal system is its ability to provide menu selection tailored to users' dietary preferences, real-time order tracking, and detailed nutritional information for each menu item. This provides users with transparency regarding the nutritional composition of their meals, supporting their efforts to adopt a more informed, healthy diet. Furthermore, the system allows consumers to order food easily and quickly, anytime and anywhere, through a responsive web platform. Therefore, the development of the FitMeal system is expected to be an effective digital solution for providing more efficient and reliable healthy catering services. Overall, this system has the potential to significantly contribute to improving the quality of life for modern society by facilitating access to healthy food choices.